THE EFFECTIVENESS OF WORDWALL APPLICATION IN ENGLISH LEARNING AT FIFTH GRADE SDN 4 BALANGNIPA - Wahdaniar, Wahdaniar; Musriani, Musriani; Firdaus, Adistya Rozita; Harmilawati, Harmilawati (Program Studi Pendidikan Bahasa Inggris Fakultas ilmu Budaya, 2025)
This study examines the effectiveness of the Wordwall application in enhancing English vocabulary learning among fifth-grade students at SDN 4 Balangnipa. Using a quantitative approach with an experimental research design, the study involved 21 students who were assessed through pre-test and post-test evaluations, classroom observations, and questionnaires. Results demonstrated a significant improvement in students' vocabulary acquisition after implementing the Wordwall application, with post-test scores showing marked increases compared to pre-test scores. Statistical analysis using Paired Sample T-Test yielded a significance value of 0.000, indicating that the Wordwall application is highly effective for vocabulary instruction. Classroom observations revealed increased student engagement and enthusiasm during learning activities, while questionnaire responses showed positive student attitudes toward the interactive learning medium. The findings suggest that the Wordwall application provides an engaging, interactive platform that effectively enhances vocabulary acquisition through gamified learning experiences. This research contributes to the growing body of evidence supporting technology-based applications as valuable tools for vocabulary instruction in elementary education settings